2013
DOI: 10.1111/jre.12083
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis increases vascular cyclooxygenase‐2: potential effect on vascular tone

Abstract: Periodontitis increases vascular COX-2 expression, which is important in the maintenance of vascular homeostasis in this model. Despite the limitations of an animal study, these findings may have important implications regarding the safety of using selective COX-2 inhibitors in patients with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
5
7
0
1
Order By: Relevance
“…We have previously shown that COX-2-derived prostanoids have an important role in periodontal disease, as treatment of rats with etoricoxib, a specific COX-2 inhibitor, results in decreased alveolar bone loss secondary to ligature-induced periodontitis (Holzhausen, Spolidorio, Muscará, Hebling, & Spolidorio, 2005). Using the same model, although placing four ligatures instead of one, Brito et al (2013) have shown that on the 28th day after the induction of periodontitis, thee is a transient systemic and vascular inflammation that leads to impaired endothelium-dependent vasodilatation, and that on the 21st day, increased COX-2 expression ocurs in mesenteric vessels, which endothelial function is worsened by treatment with etoricoxib (Mendes et al, 2014). In this way, the present study not only confirms previous observations but also strengthens the important relationship that exists between PD and endothelial dysfunction, as differently from the long-lasting, more aggressive and generalized periodontal inflammation studied by the above mentioned authors, in our model, data were collected just 7 days after placement of a single ligature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that COX-2-derived prostanoids have an important role in periodontal disease, as treatment of rats with etoricoxib, a specific COX-2 inhibitor, results in decreased alveolar bone loss secondary to ligature-induced periodontitis (Holzhausen, Spolidorio, Muscará, Hebling, & Spolidorio, 2005). Using the same model, although placing four ligatures instead of one, Brito et al (2013) have shown that on the 28th day after the induction of periodontitis, thee is a transient systemic and vascular inflammation that leads to impaired endothelium-dependent vasodilatation, and that on the 21st day, increased COX-2 expression ocurs in mesenteric vessels, which endothelial function is worsened by treatment with etoricoxib (Mendes et al, 2014). In this way, the present study not only confirms previous observations but also strengthens the important relationship that exists between PD and endothelial dysfunction, as differently from the long-lasting, more aggressive and generalized periodontal inflammation studied by the above mentioned authors, in our model, data were collected just 7 days after placement of a single ligature.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins, thromboxanes and prostacyclin from both type-1 and -2 cyclooxygenase (COX) isoforms are the major vasoactive eicosanoids (Katusi c & Shepherd, 1991), and the balance between platelet-derived thromboxane A 2 and endothelial prostacyclin is an important factor for the maintenance of vascular homeostasis (Sellers & Stallone, 2008). Previous studies have shown an increased COX-2 expression in mesenteric vessels and a transient systemic and vascular inflammation in animals with a 28 days of bilateral mandibular and maxillary ligatureinduced periodontitis (Brito et al, 2013;Mendes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the levels of MMP-9 in gingival crevicular fluid have been used to diagnose the progression of periodontitis (Sorsa et al 2006). COX-2 is also known to contribute to the development of periodontitis as it is a key mediator maintaining vascular homeostasis (Mendes et al 2014). SHI has been previously reported to down-regulate IL-1 and TNF-a expression in the joints of arthritic mice Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, despite lasting systemic and vascular inflammation, impairment in the acetylcholine response is restored 21 days onwards after the procedure. 2 , 24 Since endothelium-dependent relaxation is the main mechanism for assessing endothelial dysfunction, 5 the compensatory effect could mask a lack of NO and an increased risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%